Formation Of Creative Abilities In Students Based On Acmeological Approach - Isroilov, Qobiljon Toshtemirovich (Genius Journals, 2022)
The training of highly qualified professionals in accordance with international standards is largely related to the sustainable development of vocational education and the training of pedagogical personnel. In turn, it is necessary to implement the educational process by creating advanced pedagogical technologies, applying an acmeological approach, which leads to the need to organize the educational process taking into account the requirements of the market economy, introducing relevant educational technologies and constantly improving the content of the educational process. This issue is important for the development of creative abilities, which in the future will become an important part of educating a harmonious person in the process of training specialists, studying them from a pedagogical point of view and introducing them to a new level of quality. The article presents educational and methodological guidelines used to improve creative abilities, scientific and theoretical interpretation of factors that ensure their effectiveness, the use of acmeological approach technologies proposed to solve problems, the development of effective methods and tools, and improving the effectiveness and quality of the educational process in vocational education.
Keywords: Creative abilities; effective methods; efficiency; personal creative